Early maladaptive schemas from child maltreatment in depression and psychotherapeutic remediation: a predictive coding framework - Ramamurthy, Gita; Chen, Alan (Frontiers in Psychiatry, 2025)
Schemas are affective-cognitive conceptual models of self, others and the world, derived from life experience. Predictive Coding theory proposes schema are created from perceptual input as follows: Based on previous similar experiences, the brain generates schema, with “predictions,” expectations of future sensory experiences. Discrepancy between predicted versus actual experience produces a “prediction error.” Exposure to prediction errors considered more certain than the predictions of a schema prompts the hippocampus to update and revise the schema. Hypothesized underlying mechanisms include memory reconsolidation, extinction and pattern separation. Depression is characterized by negative schemas predicting helplessness, hopelessness and worthlessness. Early maladaptive schemas, from childhood, are implicated in mediating the greater risk of depression from childhood maltreatment. Prominent examples include the Defectiveness/Shame self-schema, predicting a flawed, unlovable self and the Social Isolation/Alienation schema, predicting isolation. Predictive Coding offers the following biopsychosocial hypothesis explaining how childhood maltreatment promotes depressogenic early maladaptive schema, and how psychotherapy can help: Schema can be difficult to change because of an attention/memory bias away from schema-incongruent information that generate prediction errors prompting schema revision. Childhood maltreatment exacerbates this learning bias. Maladaptive coping styles associated with childhood maltreatment, decrease exposure to experiences contradicting depressogenic schema. Biological changes from childhood maltreatment, including inflammation, interfere with hippocampal updating of schema. Finally, impaired socio-occupational function, associated with childhood maltreatment, reinforces depressogenic schema. By targeting factors associated with childhood maltreatment, which reinforce depressogenic early maladaptive schema or diminish prediction errors, psychotherapy can facilitate revision of depressogenic schema.